The Effect of the Fraud Hexagon Element on the Potential for Fraud in Village Fund Management with Religiosity as a Moderating Variable - Septiani, Leni Duwi; Bhilawa, Loggar (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of the fraud hexagon elements on the potential for fraud in village fund management with religiosity as a moderating variable. A sample of 200 village officials in Trenggalek Regency was analyzed using PLS-SEM through SmartPLS 4.0. The results showed that the effectiveness of the internal control system and apparatus competence had a significant positive effect, while organizational culture and political connections had a significant negative effect. Compensation suitability and apparatus morality did not have a significant effect. Religiosity only moderated the relationship between the effectiveness of the internal control system and fraud, but did not moderate the relationship between compensation suitability, organizational culture, apparatus competence, apparatus morality, and political connections.